On Kirk's strong convergence theorem for multivalued nonexpansive mappings on CAT(0) spaces - S. Dhompongsa (2018)
We prove a strong convergence theorem for multivalued nonexpansive mappings which includes Kirk's convergence theorem on CAT(0) spaces. The theorem properly contains a result of Jung for Hilbert spaces. We then apply the result to approximate a common fixed point of a countable family of single-valued nonexpansive mappings and a compact valued nonexpansive mapping. © 2011 Elsevier Ltd. All rights reserved.